2004
DOI: 10.1086/382147
|View full text |Cite
|
Sign up to set email alerts
|

Thes‐Process in Metal‐Poor Stars: Abundances for 22 Neutron‐Capture Elements in CS 31062‐050

Abstract: The CH star CS 31062-050 (½Fe=H ¼ À2:42) is one of the most useful stars yet discovered for evaluating the s-process in metal-poor stars. It is very abundant in heavy elements (e.g., ½La=Fe ¼ 2:2), and its relatively cool temperature and low gravity mean that there are many lines of interesting elements present in the spectrum. We measured the abundances of 22 elements with Z ! 29, including the rarely measured Lu and Pd. We derive an upper limit on the Th abundance as well. The abundances in CS 31062-050 show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 88 publications
2
80
4
Order By: Relevance
“…These scenarios are supported by the predictions of Bisterzo et al (2006) which satisfactorily reproduce the general features of CEMP-rs neutron-capture patterns by assuming in their model an initial high r-process enrichment before slow neutron capture begins. In contrast, Johnson & Bolte (2004) and Masseron (2006) do not find a satisfactory combination of r-and s-process that reproduce the neutron-capture element pattern in CEMP-rs stars, and call for a modified neutroncapture process. In addition, the large number of CEMP-rs stars observed at low metallicities casts doubt on the likelihood of two-phase scenarios.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…These scenarios are supported by the predictions of Bisterzo et al (2006) which satisfactorily reproduce the general features of CEMP-rs neutron-capture patterns by assuming in their model an initial high r-process enrichment before slow neutron capture begins. In contrast, Johnson & Bolte (2004) and Masseron (2006) do not find a satisfactory combination of r-and s-process that reproduce the neutron-capture element pattern in CEMP-rs stars, and call for a modified neutroncapture process. In addition, the large number of CEMP-rs stars observed at low metallicities casts doubt on the likelihood of two-phase scenarios.…”
Section: Introductionmentioning
confidence: 81%
“…Following this argument, Johnson & Bolte (2004) failed to reproduce in detail the extensive abundance pattern observed in the CEMP-rs star CS 31062-50 by adding an s-process pattern to an r-process pattern. Furthermore, Masseron (2006) demonstrated that the addition of Ba and Eu abundances as observed in CEMP-s stars (representing the contribution of a low-metallicity AGB star) to the Ba and Eu abundance as observed in rII stars (representing the contribution of a low-metallicity massive star) falls below the amount of Ba and Eu observed in CEMP-rs stars.…”
Section: The Possible Nature Of the Companions To Cemp-rs Starsmentioning
confidence: 99%
“…The atomic lines were selected from previous abundance determinations of the heavy elements of stars, namely Sneden & Parthasarathy (1983), , Sneden et al (1996), Reddy et al (1997), Aoki et al (2001Aoki et al ( , 2002b, Cowan et al (2002), Sivarani et al (2004), and Johnson & Bolte (2004). The log gf values are primarily adopted from high-precision laboratory measurements; references are given in Table 2.…”
Section: Line Selection and Atomic Datamentioning
confidence: 99%
“…These examples suggest a significant contribution from the r-process to Eu. (An alternative possibility is a contribution of the s-process with a quite different condition, e.g., with very high neutron density; Johnson & Bolte 2004). However, the [Ba/Eu] of these objects is still much higher than that of the r-process-element-enhanced stars (½Ba/Eu $ À0:8; e.g., Sneden et al 1996Sneden et al , 2003.…”
Section: Sample Stars and Their Compositionsmentioning
confidence: 99%